Sowing the Seeds of Progress: The Agricultural Biotechnology Debate in Africa - Zerbe, Noah (History compass, 2008)
Recent innovations in agricultural biotechnology raise a number of questions for the future of farming in both the developed and developing worlds. Conflicting international agreements, particularly tensions between the World Trade Organization's Trade Related Intellectual Property Rights Agreement and the Convention on Biological Diversity, provoke debates between farmers, plant breeders, and indigenous communities over the extent of ownership rights in genetic resources. Further, trade disputes between the United States and the European Union help to shape the terrain on which biotechnology is developed. The future of agricultural biotechnology in Africa is largely a function of the outcome of these debates.